2011
DOI: 10.4049/jimmunol.1002940
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer-Derived Galectin-1 Mediates Dendritic Cell Anergy through Inhibitor of DNA Binding 3/IL-10 Signaling Pathway

Abstract: Lung cancer, one of the leading causes of death worldwide, is often associated with a state of immune suppression, but the molecular and functional basis remains enigmatic. Evidence is provided in this paper supporting the role of lung cancer-derived soluble lectin, galectin-1, as a culprit in dendritic cell (DC) anergy. We have shown that galectin-1 is highly expressed in lung cancer cell lines, together with the serum and surgical samples from lung cancer patients. Functionally, lung cancer-derived galectin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 38 publications
5
74
0
3
Order By: Relevance
“…High IL-10 signaling during DC differentiation also could be one of the causes for increased ID3 expression in Wnt5a-DCs, which in turn would account for the higher capacity of Wnt5a-DCs to secrete IL-10. In support of this hypothesis, IL-10 signaling increases ID3 expression, and ID3 overexpression enhanced IL-10 production in CD14 + monocytes, thus establishing a positive feedback in the regulation of these genes (46). In agreement, high ID3 expression is characteristic of TGF-b/IL-4 activated M2 macrophages that express increased levels of IL-10 (47).…”
Section: Discussionmentioning
confidence: 84%
“…High IL-10 signaling during DC differentiation also could be one of the causes for increased ID3 expression in Wnt5a-DCs, which in turn would account for the higher capacity of Wnt5a-DCs to secrete IL-10. In support of this hypothesis, IL-10 signaling increases ID3 expression, and ID3 overexpression enhanced IL-10 production in CD14 + monocytes, thus establishing a positive feedback in the regulation of these genes (46). In agreement, high ID3 expression is characteristic of TGF-b/IL-4 activated M2 macrophages that express increased levels of IL-10 (47).…”
Section: Discussionmentioning
confidence: 84%
“…We have reported that lung cancer-derived galectin-1 causes DCs anergy in cancer microenvironments (16). We further investigated whether galectin-1 is involved in lung cancer-mediated HB-EGF up-regulation.…”
Section: Resultsmentioning
confidence: 95%
“…We demonstrated previously that lung cancer is capable of modifying the DC phenotype and impair DC function by expressing elevated levels of galectin-1 (16). Galectin-1 has also been implicated in regulating immune responses by controlling T cell survival, cytokine secretion, and transendothelial migration (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that psoriasis patients have low expression of gal-1 in peripheral blood myeloid DCs and in LCs of lesional and non-lesional skin that together with previous studies in animal models [34] indicate an important role of gal-1 in the immunopathogenesis of psoriasis. The positive role of gal-1 in IL-10 production has been proposed as one of the mechanisms involved in the inhibition of Th1 and Th17 responses [34][35][36] The co-culture experiments showed that galectin inhibition increases IFN-gamma production by CD4+ T cells in response to antigen presentation by DCs, suggesting that galectins also regulate the production of pro-inflammatory cytokines. Interestingly, IFN-gamma production was decreased by addition of recombinant gal-1 to autologous co-cultures of PBLs with moDCs from psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%